If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4b + -7 = 3b Reorder the terms: -7 + 4b = 3b Solving -7 + 4b = 3b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-3b' to each side of the equation. -7 + 4b + -3b = 3b + -3b Combine like terms: 4b + -3b = 1b -7 + 1b = 3b + -3b Combine like terms: 3b + -3b = 0 -7 + 1b = 0 Add '7' to each side of the equation. -7 + 7 + 1b = 0 + 7 Combine like terms: -7 + 7 = 0 0 + 1b = 0 + 7 1b = 0 + 7 Combine like terms: 0 + 7 = 7 1b = 7 Divide each side by '1'. b = 7 Simplifying b = 7
| 105-4x=14x+17 | | 4(w+3)=3(4+m) | | 2(x+9)-5=1 | | 8t^2-7t=0 | | 31+67=x | | 2(x+31)=(6x-22) | | 2x--9=13 | | 2x+5y+30=0 | | 4x-2(3x-2y)=3x-18 | | 68+72+x=180 | | 3p-7=12p+2 | | x^2+x-y^2=0 | | [1-7(1-5)]= | | 6x-2.1=9.3 | | 3x+x+1+x=180 | | 8a+4=5a+19 | | 6x-(x-9)= | | x^2-30x-75=0 | | 48+86+x=180 | | -(4x-1)= | | -126/9=21 | | (-2)(3)+32= | | 2x+x+x+1=180 | | 7p+13-16p+37= | | 30=6/-2 | | -9(x-3)-3=24 | | (6x-22)-(x+31)=Y | | 12d-2d(8+6e)+11de=0 | | 8c=48 | | -4x-14=2 | | 51+2x+x=180 | | -13(z-3)= |